(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2019)
Creativity and human development are two topics of research in which Behavior Analysis had active contributions. However, since these contributions occurred in parallel, there is little dialogue between behavioral approaches to creativity and development. In the present essay, such approximation is made, indicating converging points between researches on both themes. As a result of this approach, the behavior tree is presented, a schematic diagram for the purpose of planning behavioral interventions. The response tree is a diagram that spells out and maps the individual behavioral repertoire, taking into account phylogenetic, ontogenetic, and cultural variables that enable the design of teaching programs that foster creativity (i.e. new and functional behavior). Implications and advantages of adopting this type of intervention planning diagram are discussed at the end.